Pemodelan Tsunami Sederhana dengan Menggunakan Persamaan Differensial Parsial - Palupi, Indriati Retno; Raharjo, Wiji; Wibowo, Eko; Hamdalah, Hafiz (Department of Physics, Sebelas Maret University, 2018)
One way to solve fluid dynamics problem is using partial differential equation. By using Taylor expansion, fluid dynamics can be applied simply. For the example is tsunami wave. It is include to hyperbolic partial differential equation, tsunami wave propagation can describe in space and time function by using Euler FTCS (Forward Time Central Space) formula.